The effect of Plasmodium falciparum on cognition: a systematic review. - Kihara, M; Carter, J; Newton, C (2006)
OBJECTIVE: Systematic review to investigate the relationship between Plasmodium falciparum infection and cognitive function. METHOD: We searched MEDLINE, EMBASE and PsycINFO, and hand-searched journals and PhD theses. The inclusion criteria were (1) use of standardized tests for the specific populations and/or appropriate controls; (2) clear differentiation between children and adults. Eighteen studies were eligible, of which three gave information on all cognitive domains considered in the review. RESULTS: Deficits in attention, memory, visuo-spatial skills, language and executive functions may occur after malaria infection. These deficits are not only caused by cerebral falciparum malaria, but also appear to occur in less severe infections. P. falciparum seems to affect the brain globally, not in a localised fashion. Outcome depends on both biological and social risk factors. CONCLUSION: Future research should seek to establish the extent of these cognitive deficits using culturally appropriate techniques and well-defined criteria of disease.